Do you "like" my tweets? Exploring verbal and visual cues in traveler's dual-coding process - Luo, Yi; Zheng, Jie; Tang, Liang Rebecca; Wang, Xi; Yang, Lei (Journal of travel & tourism marketing, 2025)
Grounded in the dual-coding theory, this study explores the nuanced factors influencing individuals' travel intentions during the COVID-19 crisis. Utilizing sophisticated text mining and deep learning techniques on a corpus of travel-related tweets, three verbal cues (nature, humanities, tourism services), and five visual cues (foods, people, scenery, pandemic control, promotion) were identified. Findings reveal that most visual cues, such as food, people, and pandemic control, positively impact the appeal of travel tweets, while promotion has a negative effect. Among the verbal cues, nature and humanities contribute positively to likes, whereas tourism services show a negative influence.